Guru Pendidikan Agama Kristen: Pemimpin Kristen Tanpa Batas - Yenni Kornelisa Selan; Semuel Linggi Topayung (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
A Christian Religious Education teacher is a leader who never knows what it means to be tired in any situation where a teacher wants to make his students succeed in achieving a desired goal, of course the goal in question is good, such as achieving an ideal. Teachers as producers of a generation of great leaders are educated by great teachers, teachers must instill leadership values ​​for their students, both from material or direct practice in scouting extracurricular activities and so on. PAK teachers are a very noble and important profession in forming a generation that can lead the nation and state in the future, a teacher does not only act as a teacher, but also as a leader who can be a role model for his students. Leadership remains the most important part of human life, leaders are identical to teachers, when he learns from great people then he has the potential to become a great leader. Therefore, the role of PAK teachers is very important in order to produce a generation of leaders, especially in Indonesia, teachers must be prosperous so that they focus on teaching and educating their students. Teachers must focus on teaching and becoming great leaders among their students.